2022
DOI: 10.1002/anie.202204395
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent and Selective Degrader for USP7

Abstract: The tumor suppressor p53 is the most frequently mutated gene in human cancer and more than half of cancers contain p53 mutations. The development of novel and effective therapeutic strategies for p53 mutant cancer therapy is a big challenge and highly desirable. Ubiquitin‐specific protease 7 (USP7), also known as HAUSP, is a deubiquitinating enzyme and proposed to stabilize the oncogenic E3 ubiquitin ligase MDM2 that promotes the proteosomal degradation of p53. Herein, we report the design and characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…USP7 is known to stabilize the oncogenic E3 ubiquitin ligase mouse double minute 2 homolog (MDM2) that promotes the proteasomal degradation of p53 [ 108 ]. A recent study revealed that the USP7-degrading proteolysis targeting chimera (PROTAC) maintained potent cell growth inhibition in p53 mutant cancer cells, suggesting USP7-PROTAC as a promising method for potential p53 mutant cancer therapy [ 109 ]. Polo-like kinase 1 (PLK1) is a master mitotic regulator regulating DNA damage, the G2/M checkpoint, cell death pathways, and replication stress response [ 110 ].…”
Section: Degradation Of Critical Proteins In Dna Damage Repair-mediat...mentioning
confidence: 99%
“…USP7 is known to stabilize the oncogenic E3 ubiquitin ligase mouse double minute 2 homolog (MDM2) that promotes the proteasomal degradation of p53 [ 108 ]. A recent study revealed that the USP7-degrading proteolysis targeting chimera (PROTAC) maintained potent cell growth inhibition in p53 mutant cancer cells, suggesting USP7-PROTAC as a promising method for potential p53 mutant cancer therapy [ 109 ]. Polo-like kinase 1 (PLK1) is a master mitotic regulator regulating DNA damage, the G2/M checkpoint, cell death pathways, and replication stress response [ 110 ].…”
Section: Degradation Of Critical Proteins In Dna Damage Repair-mediat...mentioning
confidence: 99%
“…When the PROTAC molecule binds to both the target protein and the E3 ubiquitin ligase, it brings them into close proximity, leading to the transfer of ubiquitin molecules from the E2 ubiquitin-conjugating enzyme to the target protein (Figure B). , The ubiquitinated target protein is then recognized and degraded by the proteasome, resulting in its elimination from the cell. PROTACs have shown great potential in preclinical and early clinical studies, and their unique mechanism of action offers advantages over traditional small-molecule inhibitors. , PROTACs act in an event-driven, substoichiometric, and catalytic manner, offering several advantages over traditional inhibitors in terms of increased potency and specificity, reduced resistance, and the potential to target previously “undruggable” proteins. , On the other hand, the combination of PROTACs with proteomics analysis has proven to be a successful method for identifying potential targets of inhibitors or natural products, indicating that PROTAC technology has become a powerful tool, not only for enhancing the potency of compounds but also for exploring their therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Proteolytic targeted chimera (PROTAC), a rapidly emerging strategy, has evolved as a novel chemical method for selective proteins degradation. , In contrast to conventional occupancy-driven small-molecule inhibitors, PROTACs are event-driven and can eliminate kinase catalytic functions and non-kinase scaffolding functions. Furthermore, PROTACs can function substoichiometrically and improve selectivity. , The PROTAC strategy targeting PLK4 is depicted in Figure B. PLK4 PROTAC consists of three parts: a warhead hijacking PLK4 protein, an E3 ligase binder specifically binding E3 ligase, and a linker conjugating these two moieties. , PLK4 PROTACs can result in polyubiquitination and the proteasomal degradation of PLK4.…”
Section: Introductionmentioning
confidence: 99%
“…Proteolytic targeted chimera (PROTAC), a rapidly emerging strategy, has evolved as a novel chemical method for selective proteins degradation. 36,37 In contrast to conventional occupancy-driven small-molecule inhibitors, PROTACs are eventdriven and can eliminate kinase catalytic functions and nonkinase scaffolding functions. 38−40 Furthermore, PROTACs can function substoichiometrically and improve selectivity.…”
Section: ■ Introductionmentioning
confidence: 99%